Development of Umum Al-Balwa Parameter for Pandemic Sop: The Fuzzy Delphi Approach - Ahmad Misbah bin Mohamad Hilmi; Muhamad Ismail bin Abdullah; Ismail bin Omar; Mohd Rofaizal bin Ibhraim; Abdul Hakim bin Baharudin @ Ismail; Muhammad bin Shaberi; Lukman Abdul Mutalib (Human Resource Management Academic Research Society, 2024)
Vol. 13, No. 7, 2023, Pg. 1091 – 1101